Research on Lexical Usage and Lexicographical Practice - Zubaitienė, Vilma (Lietuvių kalba, 2024)
The article presents research on the usage of Lithuanian lexis and lexicographical works on the Lithuanian language from the beginning of the 20th century to the present day. It reveals how scientific research has been related to academic activity and lexicographic work (data gathering, analysis, dictionary development), and vice versa. Talking about the early and mid-20th century, the focus lies on the well-grounded articles on appropriate language use by Kazimieras Būga and on the preparation of the “Dictionary of the Lithuanian Language”, as well as on Jonas Jablonskis’ interest in the standard language, creation of new words, his work on the dictionary of Antanas Juška and his reviews of earlier dictionaries. Jablonskis’ own “Mūsų žodynėlis” [Our Dictionary] is also briefly discussed. Further on, the article talks about the work of Juozas Balčikonis and the beginnings of the academic “Dictionary of the Lithuanian Language”. Particular mention is made of Pranas Skardžius’ and Antanas Salys’ research on word structure and usage. In addition, various articles in language journals as well as the structure and editorial principles of the journal “Kalbos patarėjas” are reviewed. The research in the Soviet era is mainly associated with the lexicographical activities of Jonas Kruopas and Kazys Ulvydas and the editorial work on both the (historical) “Dictionary of the Lithuanian Language” and the “Dictionary of the Present Lithuanian Language”. The research interest of this period lies primarily in the analysis of lexical structure and systemic relations, whereas publication activity focuses on editing special dictionaries (such as dictionaries of synonyms, antonyms, valency, phraseology, and comparisons), and the publication of textbooks and monographs in the field of lexicology. The article gives an overview of studies that analyse the development and change of various lexical items, describe different semantic groups, language variation, and its phrasal components. Furthermore, lexical databases and the information system e.kalba are given an overview. The main focus here lies on reviewing lexical research and lexicographical projects carried out in the 1990s and the early 21st century, and on revealing lexicographical problems.